THE URGENCY OF RELIABILITY IN THE EVALUATION OF ISLAMIC R THE EFFORTS OF THE COUNSELING GUIDANCE TEACHER IN DISCIPLINING GRADE 8 STUDENTS THROUGH CONGREGATIONAL PRAYER AT SMP MUHAMMADIYAH 1 SURAKARTA - Hibatulloh, Syamsudin Nawwar; Anshari, Ari (Institut Islam Mamba'ul 'Ulum Surakarta, 2024)
In an educational institution, it must have its own problems. The current phenomenon is that many students are not disciplined in school activities. Students sometimes do not obey the rules or rules that exist in schools, so this is a problem in every educational institution. The school management needs to solve this kind of problem. Especially this guidance and counseling teacher plays an important role in disciplining his students. Therefore, teachers at school as role models for their students. When the teacher is orderly and teaches according to what has been planned by the school, it will make the students orderly. The expected purpose of this study is to describe the efforts of BK teachers in disciplining students and identify the obstacles of BK teachers in disciplining grade 8 students through the implementation of dhuha prayers at Smp Muhammadiyah 1 Surakarta. This study used descriptive qualitative research. This descriptive qualitative research is research that seeks to describe the rehearsals, events, and events that occur today. The result of this study is that bk teachers provide advice, motivation, guidance and sanction students to be disciplined. In disciplining students, bk teachers provide direction, advice, and motivation so that students are aware of the importance of discipline in the school environment, especially in matters of congregational prayer